A Country Strange and Far : The Methodist Church in the Pacific Northwest, 1834-1918 - McKenzie, Michael C. (Book collections on Project MUSE., 2022)
"In 1834 the weary missionary Jason Lee arrived on the banks of the Willamette River and began to build a mission to convert the local Kalapuya and Chinook populations to the Methodist church. The denomination had become a religious juggernaut in the United States, dominating the religious scene throughout the mid-Atlantic and East Coast. But despite its power and prestige and legions of clergy and congregants, Methodism fell short of its goals of religious supremacy in the northwest corner of the continent.In A Country Strange and Far Michael C. McKenzie considers how and why the Methodist church failed in the Pacific Northwest and how place can affect religious transplantation and growth. Methodists failed to convert local Native people in large numbers, and immigrants who moved into the rural areas and cities of the Northwest wanted little to do with Methodism. McKenzie analyzes these failures, arguing the region itself-both in the natural geography of the place and in the immigrants' and clergy's responses to it-was a primary reason for the church's inability to develop a strong following in the Northwest. The Methodists' efforts in the Pacific Northwest provide an ideal case study for McKenzie's timely region-based look at religion. "--